Local Government and Community Development (LGCD), Baitul Makmur Medan Raya, Petra Jaya / Khatijah Mostapha - Mostapha, Khatijah (Universiti Teknologi MARA, Sarawak, 2013)
The Ministry of Local Government and Community Development (LGCD) is entrusted with the responsibility to ensure that the Local Authorities exercise their powers within the provisions of the relevant laws and to ensure sufficient funding from both the State and Federal Governments to assist the Local Authorities to implement development programs. Moreover, it is also the responsibility of LGCD to ensure that local authorities prepare realistic budgets and that their expenditures are audited and within their financial capabilities. LGCD is under the charge of Senior Minister, Y.B. Dato Sri Wong Soon Koh and ably assisted by three (3) Assistant Ministers, namely (i) Y.B. Datuk John Sikie Tayai (Rural District Council), (ii) Y.B. Datuk Peter Nansian Ngusie (Community Development), and (iii) Y.B. Dr Jerip Susil (Public Health). Dr Penguang Manggil, the Permanent Secretary is assisted by a Legal Adviser, Encik Francis Johen Ak Adam, three (3) Principal Assistant Secretaries, Puan Susan Loh (Development), Encik Shariman Faizul Abdullah (Community Development and Public Health) and Puan Norleha Haji Shariff (Administration, Finance, HRM (PBT) and ICT).